2019
DOI: 10.4103/nmj.nmj_53_19
|View full text |Cite
|
Sign up to set email alerts
|

Components and risk factors of metabolic syndrome among rural Nigerian workers

Abstract: Background: Metabolic syndrome (MetS) is a serious public health risk predisposing the workforce to cardiovascular diseases and diabetes. Aim: The aim of this study was to determine the components and risk factors of MetS among Nigerian teachers and bank workers (BWs). Settings and Design: The cross-sectional study was conducted in Idemili South Local Government Area, Southeast Nigeria. Materials and Methods: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…The Low high-density lipoprotein-cholesterol level as the most prevalent dyslipidemia in the present study is similar to what was reported among Northern Mexican adolescents [42], but the result is in contrast to the reported abdominal obesity, raised diastolic blood pressure and hyper triglyceridemia as determinants of metabolic syndrome in rural workers from Idemili South Local Government Area, Southeast Nigeria [21].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The Low high-density lipoprotein-cholesterol level as the most prevalent dyslipidemia in the present study is similar to what was reported among Northern Mexican adolescents [42], but the result is in contrast to the reported abdominal obesity, raised diastolic blood pressure and hyper triglyceridemia as determinants of metabolic syndrome in rural workers from Idemili South Local Government Area, Southeast Nigeria [21].…”
Section: Discussionsupporting
confidence: 87%
“…Prevalence of elevated TRIG in the male (16.51%) and female (15.69%) subjects in the present study is lower compared to the prevalence of 38.0% reported for rural workers from Idemili South Local Government Area, Southeast Nigeria [21].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This work is in line with a study reported in Nigeria. 27 The high prevalence of MetS among females was previously reported in the African populations. [34][35][36][37] In the African population the waist circumference is a crucial determinant factor of MetS.…”
Section: Discussionmentioning
confidence: 73%
“…14 The finding of the current study is consistent with the pooled review among a healthy adult population in Ghana with the mean age of 36.7 years and a cross-sectional study conducted in Nigeria involving teachers and bank workers that found an incidence of 20-21.5% in working adults. 26,27 The prevalence of MetS in the working adults was much higher than the prevalence of 4.8% reported in a national survey in Ethiopia, 10 but the national survey had 88.5% of participants from rural areas. The high prevalence of MetS in our study could be due to a more sedentary lifestyle, increased pressure from the high work load, and changes in dietary patterns.…”
Section: Discussionmentioning
confidence: 74%